Boiler system modelling using Flownex® - Rossouw, André (Department of Mechanical Engineering, 2016)
The objective of this project is to develop a boiler modelling methodology, specifically using Flownex, which is capable of running transient simulations for a large variety of coal-fired boiler designs typically used in Eskom. Flownex has been identified as the key software to accomplish the global objective of the Centre for Energy Efficiency under EPPEI at the University of Cape Town, which is to develop a software model of a complete coal-fired power station which includes all the main systems required for independent transient simulation. The boiler model captures the true geometric layout and flow orientation with associated characteristics of a wide variety of boiler designs utilised by Eskom. In order to achieve this, boilers and heat exchangers are grouped according to common physical properties which simplify the modelling process and optimise results. This is preceded by an investigation into the types of boiler designs currently operational in Eskom including available associated geometrical and process characteristics. A study into heat transfer mechanisms applicable to coal-fired boiler heat exchangers was done to ensure fundamental theoretical principles are adhered to during the development of the analytical models, the first step in the modelling process. The Flownex solving methodology is evaluated against the analytical models in a simplified heat exchanger before full detail modelling of heat exchangers are done. The component and method used in Flownex requires convection and radiation heat transfer to be accounted for separately and thus heat exchangers are classified sequentially according to their location in the boiler, this process relies heavily on data obtained in the boiler study. Heat exchangers and auxiliary systems are then integrated into a single system used to obtain steady-state results. The steady-state boiler model is evaluated against actual boiler design data for various loads to prove applicability to various boiler designs and operating conditions.